2020
DOI: 10.1097/adm.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

A Case of False-positive Amphetamine Results on Urine Toxicology Testing Secondary to Imatinib

Abstract: In this case report, we describe a case of imatinib leading to a false-positive amphetamine result on urine drug testing. A 21-year-old female with chronic myelocytic leukemia and in recovery from opioid use disorder reinitiated imatinib maintenance therapy in her third trimester, after previous discontinuation at the beginning of pregnancy. Subsequently, she had multiple presumptive immunoassay-based urine drug tests that resulted positive for amphetamines. The infant's meconium testing was negative for amphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In drugs‐of‐abuse studies and applied toxicology testing, initial identification of drugs and their metabolites in biological fluids is most often performed by immunoassay methods that provide only qualitative and presumptive evidence of drug classes. Although studies have shown a significant incidence of both false positives and false negatives by presumptive immunoassay screening techniques, more sensitive and selective methods of definitive drug identification by LC‐ESI‐MS/MS continue to be reserved for use in more limited confirmation and quantitation testing (Darragh, Snyder, Ptolemy, & Melanson, 2014; Macher & Penders, 2012; Manchikanti, Malla, Wargo, & Fellows, 2011; Meyers & Wachman 2010; Mikel, Pesce, Rosenthal, & West, 2012; Pesce et al., 2010; Saitman, Park, & Fitzgerald, 2014; West et al., 2010). With more recent advances in automated drug testing by LC‐MS technology, it is instrumentally possible to employ direct‐to‐definitive methods of high‐volume drug testing in both basic and applied toxicology studies.…”
Section: Commentarymentioning
confidence: 99%
“…In drugs‐of‐abuse studies and applied toxicology testing, initial identification of drugs and their metabolites in biological fluids is most often performed by immunoassay methods that provide only qualitative and presumptive evidence of drug classes. Although studies have shown a significant incidence of both false positives and false negatives by presumptive immunoassay screening techniques, more sensitive and selective methods of definitive drug identification by LC‐ESI‐MS/MS continue to be reserved for use in more limited confirmation and quantitation testing (Darragh, Snyder, Ptolemy, & Melanson, 2014; Macher & Penders, 2012; Manchikanti, Malla, Wargo, & Fellows, 2011; Meyers & Wachman 2010; Mikel, Pesce, Rosenthal, & West, 2012; Pesce et al., 2010; Saitman, Park, & Fitzgerald, 2014; West et al., 2010). With more recent advances in automated drug testing by LC‐MS technology, it is instrumentally possible to employ direct‐to‐definitive methods of high‐volume drug testing in both basic and applied toxicology studies.…”
Section: Commentarymentioning
confidence: 99%